Engineering revolution : the paradox of democracy promotion in Serbia - Spoerri, Marlene (University of Pennsylvania Press, 2014)
Drawing from declassified CIA documents, personal interviews, and internal NGO documents, Engineering Revolution uncovers the true extent of the West's involvement in the overthrow of Balkan dictator Slobodan Miloševic´--finding that Western governments often hurt, rather than helped, Serbia's tenuous transition to democracy.